Implemntasi Supervisi Akademik Di SD Negeri Pelita Jaya Dalam Meningkatkan Kompetensi Pedagogik Guru - Rubi Babullah; Siti Qomariyah; Neneng Neneng; Ujang Natadireja; Siti Nurafifah (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to investigate efforts to increase teacher pedagogical competence through academic supervision at SDN Pelita Jaya. The research method used is a qualitative approach with data collection techniques in the form of interviews, observation and document analysis. Respondents in this study were school principals, teachers and school supervisors. Data analysis is carried out through the process of data reduction, data display, conclusion and data verification. Research findings show that the implementation of academic supervision at SDN Pelita Jaya has made a significant contribution to improving teacher pedagogical competence. Academic supervision facilitates a process of reflection, constructive feedback, and ongoing professional development. However, research also identifies several barriers to implementing academic supervision, such as limited resources, resistance from some teachers, and challenges in adapting to curriculum changes. As a solution, research recommends strengthening leadership support, increasing access to training, and implementing a collaborative approach in developing teacher pedagogical competence. The implication of this research is the importance of strengthening academic supervision practices as an effective strategy in improving the quality of learning and student learning outcomes at SDN Pelita Jaya.